Sport specialization and coordination differences in multisport adolescent female basketball, soccer, and volleyball athletes - DiCesare, C. A.; Montalvo, A.; Barber Foss, K. D.; Thomas, S. M.; Hewett, T. E.; Jayanthi, N. A.; Myer, G. D. (Journal of Athletic Training, 2019)
Context Early sport specialization, or the participation in 1 sport year-round to the exclusion of all others, is a growing concern in youth athletics because of its possible association with musculoskeletal injury. The underlying injury risk may be the result of coordination differences that sport-specialized athletes have been speculated to exhibit relative to multisport athletes; however, little evidence exists to support or refute this notion.